Fixed-order gain-scheduling anti-sway control of overhead bridge cranes. (November 2016) - Ermidoro, Michele; Cologni, Alberto L.; Formentin, Simone; Previdi, Fabio
Abstract: Acceleration and deceleration in overhead cranes may induce undesirable load swinging, which is unsafe for the surrounding human operators. In this paper, it is shown that such oscillatory behavior depends on the length of the rope and thus a gain-scheduling control law is proposed to reduce such an effect. Specifically, to take into account the technological limits in the controller implementation, a fixed-order controller is tuned, by also enforcing robustness and performance constraints. The proposed strategy is experimentally tested on a real bridge crane and compared to a time-invariant solution.